2016
DOI: 10.1080/21551197.2015.1125325
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk is Associated with Chronic Musculoskeletal Pain in Community-dwelling Older Persons: The PAINEL Study

Abstract: Malnutrition is a risk factor for noncommunicable diseases related to ageing, and it can also contribute to musculoskeletal health. This study investigated whether nutritional risk is associated with chronic musculoskeletal pain in community-dwelling older persons. Nutritional risk was assessed by the DETERMINE Checklist. Chronic musculoskeletal pain was defined as the presence of pain in the past six months that did not disappear for at least 30 consecutive days. Multivariate logistic regression including con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
17
1
Order By: Relevance
“…Our results have public health implications for policy making and targeted interventions among ethnic minorities. On one hand, both excess body weight and underweight in childhood are associated with adulthood chronic diseases, including diabetes and cardiovascular diseases [ 38 – 40 ]. The customized implementation of nutrition improvement program and obesity intervention has a potential to reduce the risk of these chronic disease in minority areas.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have public health implications for policy making and targeted interventions among ethnic minorities. On one hand, both excess body weight and underweight in childhood are associated with adulthood chronic diseases, including diabetes and cardiovascular diseases [ 38 – 40 ]. The customized implementation of nutrition improvement program and obesity intervention has a potential to reduce the risk of these chronic disease in minority areas.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that nutritional risk score was independently associated with chronic musculoskeletal pain. For each additional unit of risk score, the risk of pain increased by 11% [49].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trend of obesity, both in adults and children, is directly responsible for the rapid increase in NCDs28. Moreover, malnutrition is a risk factor for NCDs related to ageing29. Thus, by reducing the prevalence of overweight and malnutrition, the burden of chronic disease can also be reduced, and the life expectancy of humans can be extended.…”
Section: Discussionmentioning
confidence: 99%